Mothers' perceptions and experiences of skin-to-skin contact after vaginal birth in Saudi Arabia: A cross-sectional study. Issue 1 (February 2022) - Abdulghani, Nawal; Cooklin, Amanda; Edvardsson, Kristina; Amir, Lisa H.
Abstract: Problem: The World Health Organization recommends immediate skin-to-skin contact after birth, however, worldwide, separation of mothers and infant is common. Background: In Saudi Arabia, there is a lack of research exploring mothers' experiences of skin-to-skin contact after birth. Aim: To estimate the rate of skin-to-skin contact and describe mothers' perceptions and experiences of immediate skin-to-skin contact after vaginal birth in two largest hospitals in Jeddah, Saudi Arabia. Methods: A cross-sectional study conducted in 2017. A total of 254 mothers completed the survey on the postnatal ward (92 % response rate). The survey consisted of 36 closed and open-ended items. Data were described using summary statistics and free text comments were analysed using content analysis. Results: The rate of direct skin-to-skin contact was 15%. A further 54% of mothers had the baby placed on their chest/abdomen but with a sheet/gown between them. Mothers reported favourable perceptions towards skin-to-skin contact and reported the practice as acceptable (67%). Most mothers did not express concerns about feeling exposed (85%) or that skin-to-skin contact was inconsistent with norms of modesty or culture (87%). The free text comments indicated that most mothers felt positive about their experience of skin-to-skin contact, while some mothers felt overwhelmed and unprepared. Discussion and Conclusions: Skin-to-skin contact was not routinely implemented after birth and the rate was low. Mothers held positive perceptions and wanted to practice skin-to-skin contact. Policy makers and clinicians should acknowledge mothers' needs and feelings by facilitating skin-to-skin contact to achieve optimal outcomes for mothers and infants.